The process of translation, adaptation, and question of feminism in Luo Guanzhong’s Romance of the Three Kingdoms - Tan Michael Chandra (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
As one of the Four Great Classic Novels of Chinese literature, Romance of the Three Kingdoms found its way to the constellation of World Literature via translation and being adapted into the movie Red Cliff (2008) and famous video games series Dynasty Warriors (1997-now). This process further made the story of the Three Kingdom is widely known as many cinemagoers and gamers can associate themselves with the story in the form that they adore. Both processes, however, have disadvantages as they erase the Chinese cultural elements that are demonstrated in the novel. This novel is also heavily riddled with patriarchal paradigm that makes scholars consider Romance of the Three Kingdoms “masculine novel” by portraying women in a very weak position in Chinese society. This paper would try to dissect the issues of translation and women portrayal in detail by analyzing the translated work of Romance of the Three Kingdoms to see what cultural aspect that is disappear as a result of translation and dissecting the dismissive and derogative portrayal of several women characters in the novel.